Diffuse large B‐cell lymphoma: a consensus practice statement from the Australasian Lymphoma Alliance. Issue 9 (21st July 2022) - Wight, Joel; Hamad, Nada; Campbell, Belinda A.; Ku, Matthew; Lee, Kenneth; Rose, Hannah; Armytage, Tasman; Latimer, Maya; Lee, Hui‐Peng; Lee, Sze‐Ting; Dickinson, Michael; Khor, Richard; et al.
Abstract: Diffuse large B‐cell lymphoma (DLBCL) is the most common lymphoma subtype, accounting for 30–40% of lymphoma diagnoses. Although aggressive, cure is achievable in approximately 60% of cases with primary chemoimmunotherapy, and in a further substantial minority by salvage therapy and autologous stem cell transplantation. Despite promising activity in early phase clinical trials, no intensified or novel treatment regimen has improved outcomes over R‐CHOP21 in randomised studies. However, there remain several areas of controversy including the most appropriate prognostic markers, central nervous system prophylaxis and the optimal treatment for patients with high‐risk disease. This position statement presents an evidence‐based synthesis of the literature for application in Australasian practice.